2021
DOI: 10.3390/su13084519
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Entrepreneurial Intention of University Students in China: Integrating the Perceived University Support and Theory of Planned Behavior

Abstract: Entrepreneurial education has always played an important role in developing entrepreneurship. In recent years, China has been emphasizing the integration of innovative entrepreneurship concepts into university curricula. Entrepreneurial education can also contribute to the sustainability of business development. In the context of “mass entrepreneurship and innovation”, entrepreneurial education is important to promote the restructuring of the economic and business model, enhance the development momentum, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 82 publications
4
55
0
8
Order By: Relevance
“…In the TPB model, Ajzen [33] suggested that perceived behavioral control can affect behavioral intentions and directly affect actual behavior, because even if a person wants to do something, doing so requires actual behavioral control. Studies have reported that behavioral control affects students' behavioral intentions [20,25,29]. Therefore, we proposed H3 as follows: H3: The behavioral control of college students significantly influences their sexual intentions.…”
Section: Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…In the TPB model, Ajzen [33] suggested that perceived behavioral control can affect behavioral intentions and directly affect actual behavior, because even if a person wants to do something, doing so requires actual behavioral control. Studies have reported that behavioral control affects students' behavioral intentions [20,25,29]. Therefore, we proposed H3 as follows: H3: The behavioral control of college students significantly influences their sexual intentions.…”
Section: Hypothesesmentioning
confidence: 98%
“…For example, sex education from family members and the transfer of sexual knowledge among friends or colleagues can change college students' views on certain behaviors (e.g., sexual behavior). Research has revealed that behavioral intentions can be influenced by both subjective factors and the environment [29][30][31][32]. Therefore, we proposed H2 as follows: H2: The subjective norms of college students significantly influence their sexual intentions.…”
Section: Hypothesesmentioning
confidence: 99%
“…One data sample consisted of a single questionnaire completed by one person. We received 385 questionnaires between August and November 2020, and 22 were excluded because they did not meet completeness and normative requirements (Su et al, 2021). In total, 363 valid questionnaires were obtained, a valid response rate of 94.28%.…”
Section: Samplementioning
confidence: 99%
“…SEM-PLS was employed for the measurement and structural model analysis mainly because it, compared with covariancebased SEM, involves analyzing the complex relationships between observed and latent variables. SEM-PLS has been widely adopted for analysis in research on marketing management, information management, organizational management, human resources management, and tourism management (Yang and Lin, 2014;Suen et al, 2019;Jin et al, 2021;Su et al, 2021).…”
Section: Measurement Modelmentioning
confidence: 99%
“…Scholars' cognition of entrepreneurial psychological factors is limited to entrepreneur's personality traits (such as autonomy, control points, achievement needs and tolerance of ambiguity), and they have not been able to find states or state-like psychology that are very different from idiosyncratic psychological factors. With the rise of social cognition theory, especially positive psychology and positive organizational behavior, the role of entrepreneurial psychology factors in the model of new venture performance determining factors will be re-recognized and positioned (Llewellyn and Wilson, 2013;Gudykunst, 2020;Hande and Faruk, 2021;Serrano et al, 2021;Su et al, 2021;van Ewijk and Weber, 2021).…”
Section: The Entrepreneur's Psychological Capitalmentioning
confidence: 99%